ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DISIPLIN KERJA APARATUR SIPIL NEGARA DI KANTOR SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN NIAS SELATAN - HAREFA, SEJAHTERA YITRO; PASARIBU, JOHNSON; PANJAITAN, FERRY (LP2MTBM MAKARIOZ, 2021)
The purpose of the study was to determine and analyze the factors that influence the work discipline of the state civil apparatus at the Secretariat Office of the Regional Representatives Council of South Nias Regency. The research method uses multiple linear regression, hypothesis testing, and coefficient of determination. The results of multiple linear regression research that attitudes, leadership roles, and emotional intelligence on work discipline in the State Civil Apparatus of the DPRD Secretariat of South Nias Regency, test the hypothesis for the F test that the role of leadership and emotional intelligence has a significant effect on work discipline in the State Civil Apparatus of the Secretariat of the Regency DPRD South Nias, for the t test, attitude was found to have a significant effect on work discipline, the role of leadership had a significant effect on work discipline, and emotional intelligence had a significant effect on work discipline. Suggestions that employees should conduct personal development training, and leaders should pay more attention to cooperative relationships with other organizations